2011
DOI: 10.1038/jhg.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

LCR-initiated rearrangements at the IDS locus, completed with Alu-mediated recombination or non-homologous end joining

Abstract: Mucopolysaccharidosis type II (MPS II) is caused by mutations in the IDS gene, which encodes the lysosomal enzyme iduronate-2-sulfatase. In B20% of MPS II patients the disorder is caused by gross IDS structural rearrangements. We identified two male cases harboring complex rearrangements involving the IDS gene and the nearby pseudogene, IDSP1, which has been annotated as a low-copy repeat (LCR). In both cases the rearrangement included a partial deletion of IDS and an inverted insertion of the neighboring regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Our breakpoint analysis suggests that Alu‐mediated intragenic recombination can be a mechanism of deletional mutation in CGL2, as reported in other loci that undergo non‐allelic homologous recombination (NAHR) following the ectopic cross‐over of repeat sequences [Oshima et al, , ; Liu et al, ]. Alignments of breakpoint sequences revealed two interesting features, raising additional mechanistic possibilities.…”
Section: Discussionsupporting
confidence: 73%
“…Our breakpoint analysis suggests that Alu‐mediated intragenic recombination can be a mechanism of deletional mutation in CGL2, as reported in other loci that undergo non‐allelic homologous recombination (NAHR) following the ectopic cross‐over of repeat sequences [Oshima et al, , ; Liu et al, ]. Alignments of breakpoint sequences revealed two interesting features, raising additional mechanistic possibilities.…”
Section: Discussionsupporting
confidence: 73%
“…In another study with Israeli families (Simon-Schiff et al, 1994), the authors identified two patients with deletions of the exons 5, 6, and 7. Oshima et al in 2011, identified two cases of rearrangements that included a partial deletion of IDS gene and an inverted insertion of the pseudogene IDSP1, probably mediated by an Alu element (Oshima et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A pseudogene ( IDSP1 —also known as IDS2 ), located telomeric to the functional IDS gene, contains sequences homologous to exon 2, intron 2, exon 3 and a chimerical fragment of intron 3–intron 7, making this region prone to the occurrence of non-allelic homologous recombination events [ 41 ]. Indeed, whole IDS gene deletion (with or without the involvement of further neighboring genes) and partial IDS exon deletions have been reported in multiple studies, mainly in patients with a severe Hunter syndrome presentation [ 41 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Furthermore, IDS exons duplications, IDS1/IDS2 inversions, chimeric IDS-IDS2 allele and other large complex rearrangements have been described [ 41 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], as well as deletions in the promoter region in patients with a mild phenotype [ 72 ].…”
Section: Svs In Lsdsmentioning
confidence: 99%